Evaluating the effect of dermaseptin S4 and its derivatives on multidrug-resistant bacterial strains and on the colon cancer cell line SW620 - Belaid, Afifa; Braiek, Afef; Alibi, Sana; Hassen, Wafa; Beltifa, Asma; Nefzi, Adel; Mansour, Hedi Ben (Environmental science and pollution research international, 2021)
Dermaseptins are peptides found in the skin secretions of Phyllomedusinae frogs. These peptides exert a lytic action on various microorganisms and have no considerable hemolytic effect except dermaseptin S4 (DS4) which exhibits a powerful cytotoxic effect. Therefore, we synthesized several analogs of DS4 in an attempt to find molecules with a weak hemolytic effect and significant bioactivities. In this study, we performed the synthesis of truncated peptides by introducing C-terminal and N-terminal amino acid deletions of the native sequence. All peptide analogs, in comparison with parental peptide, were tested firstly on human red blood cells to work out their cytotoxicity, secondly on the multidrug-resistant bacteria by trying to find MICs, and finally on colon cancer tumor cell line SW620 using the MTT test so as to investigate the anti-proliferative effect. Our results showed that, on the one hand, the N terminus of the native peptide was necessary for the antibacterial activity and the anti-proliferative effect of the peptide. On the other hand, the hemolytic activity was more notable in the sequences broken down on the C-terminal side.